"Mind the gap": to succeed in marketing politics, think of social media innovation. Issue 6 (9th September 2019) - Anim, Patrick Amfo; Asiedu, Frederick Okyere; Adams, Matilda; Acheampong, George; Boakye, Ernestina
Abstract : Purpose: This paper aims to explore the relationships between political marketing via social media and young voters' political participation in Ghana. Additionally, this study examines the mediating role political efficacy plays in enhancing the relationship. Design/methodology/approach: With a positivist mindset, and adopting the survey strategy, data gathered from the questionnaire administered from the sampled 320 young voters (18-29 years) in Greater Accra were quantitatively analyzed. An exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and structural equation modeling (SEM) were used to assess and confirm the proposed scales validity and the relationships of the research model. Findings: The study revealed that a political party or candidate's ability to achieve political participation from Ghanaian young voters' is dependent on how effective they build customer relationship or gaining visibility through social media. In addition, the study showed that political efficacy mediates the relationship between customer relationship building or gaining visibility through social media and political participation among Ghana young voters. Thus, young voters in Ghana must see themselves to have a say in the affairs of political parties through the political messages they gather from social media platforms to enhance their political participation activities. Practical implications: The results of this paper will enable political marketers and politicians not only in Ghana but across the globe, to better understand how social media as a communication tool could be used to positively influence users' political participation. Originality/value: Considering the uniqueness of this study in a Ghanaian context, this paper is the first of its kind to use the social capital theory in examining the mediating role political efficacy plays in enhancing the relationship between political marketing on social media and young voters' political participation.